Acute autonomic neuropathy in association with systemic lupus erythematosus. Issue 6 (June 1985) - Hoyle, C; Ewing, D J; Parker, A C
Abstract : A patient is described with acute autonomic neuropathy, developing post partum in association with systemic lupus erythematosus, and showing a rapid clinical response to steroids. The pattern of tissue damage is suggestive of an immunologically mediated mechanism.